2023
DOI: 10.1186/s12905-023-02486-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate impact of Mindfulness-Based Cognitive Therapy (MBCT) among women with breast cancer: a systematic review and meta-analysis

Abstract: Background Mindfulness-based cognitive therapy (MBCT) may have positive physiological and psychological benefits for breast cancer survivors. However, few studies involved a combination of the relevant literatures to confirm the effects. Methods Our study included randomized controlled trials (RCTs) and non-RCTs comparing interventions of MBCT and control protocols for alleviation of symptoms among breast cancer survivors. We calculated pooled mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Meta-analyses examining the use of MBCT in populations living with bipolar disorder (Xuan et al, 2020) and chronic pain (Pei et al, 2021) found reductions in depression in between-group comparisons with moderate effect sizes. In contrast to Chang et al (2023) meta-analysis however, Pei et al (2021) paper did not find any statistically significant improvements in measures of pain. Though two meta-analyses reported reduction in anxiety symptoms with MBCT (Ghahari et al, 2020;Xuan et al, 2020), results varied for between-group analyses: Xuan et al (2020) meta-analysis found no significant effects, as opposed to Ghahari et al (2020) meta-analysis, which noted significant decreases with moderate effect sizes.…”
Section: Mbct Evidence Basementioning
confidence: 86%
See 1 more Smart Citation
“…Meta-analyses examining the use of MBCT in populations living with bipolar disorder (Xuan et al, 2020) and chronic pain (Pei et al, 2021) found reductions in depression in between-group comparisons with moderate effect sizes. In contrast to Chang et al (2023) meta-analysis however, Pei et al (2021) paper did not find any statistically significant improvements in measures of pain. Though two meta-analyses reported reduction in anxiety symptoms with MBCT (Ghahari et al, 2020;Xuan et al, 2020), results varied for between-group analyses: Xuan et al (2020) meta-analysis found no significant effects, as opposed to Ghahari et al (2020) meta-analysis, which noted significant decreases with moderate effect sizes.…”
Section: Mbct Evidence Basementioning
confidence: 86%
“…The use of MBCT with other conditions has also been studied including anxiety ( Evans et al, 2008 ; Kim et al, 2009 ; Ghahari et al, 2020 ), bipolar disorder ( Lovas and Schuman-Olivier, 2018 ; Xuan et al, 2020 ), vascular disease ( Abbott et al, 2014 ), breast cancer ( Chang et al, 2023 ), and chronic health conditions ( Hazlett-Stevens et al, 2019 ; Pei et al, 2021 ). Meta-analyses examining the use of MBCT in populations living with bipolar disorder ( Xuan et al, 2020 ) and chronic pain ( Pei et al, 2021 ) found reductions in depression in between-group comparisons with moderate effect sizes.…”
Section: Evidence Basementioning
confidence: 99%